Flavonoid profiles of immature and mature fruit tissues of Citrus grandis Osbeck (Dangyuja) and overall contribution to the antioxidant effect. (9th September 2014) - Yu, Eun Ae; Kim, Gon‐Sup; Lee, Ji Eun; Park, Semin; Yi, Song; Lee, Soo Jung; Kim, Jae Hoon; Jin, Jong Sung; Abd El‐Aty, A. M.; Shim, Jae‐Han; Shin, Sung Chul
Abstract: Citrus fruits are a valuable functional food and their peel is used in East Asian folk medicine. In this study, the polar components of the fruit tissues of Citrus grandis Osbeck were analyzed using high‐performance liquid chromatography–tandem mass spectrometry and compared with reported data. Among the 13 characterized compounds, eight flavonoids and one coumarin were identified for the first time in fruit tissues. The total amount of the identified components was the largest for the immature fruit peel, followed by mature fruit peel, mature fruit flesh, and immature fruit flesh. Naringin (2) and neohesperidin (3) were particularly rich in all samples. The antioxidant activity of the flavonoids extracted from fruit tissues increased in a dose‐dependent manner. The activity of the fruit peels was significantly higher than that of the fruit flesh. Copyright © 2014 John Wiley & Sons, Ltd.